Thermal comfort evaluation of an operating room through CFD methodology - Rodrigues, N (2013)
Different studies have been evidencing that the surgeon, working with a high metabolic rate, feels uncomfortable after a time. This enforces the study of indoor thermal conditions in health care facilities. The main objective of the present work is the evaluation of the thermal comfort sensation experienced by surgeons and nurses inside a Portuguese orthopaedic surgical room, using the PMV index. Through CFD tools and a post-processing routine, it was obtained the PMV index in each domain node, in opposite to the typical use of average climate values. The use of average ventilation values, to calculate the index, does not provide a correct and enough descriptive evaluation of the surgical room thermal environment. It is noticeable that surgeons and nurses feel different thermal sensations in the same surgical room. For the studied case, the surgeon feels the room environment hotter than the nurse. The nurses feel a slightly cold sensation under the air supply diffuser and a neutral zone is located in the air stagnation zones close to the walls. As expected for both cases, lamps provide an uncomfortable sensation. The clothing used by both classes, as well as the ventilation conditions, shall be revised accordingly to the amount of persons in the room and the type of activity performed.